Organizing work in local service implementation: an ethnographic study of nurses' contributions and competencies in implementing a municipal acute ward - Helle Krone-Hjertstrøm; Bente Norbye; Birgit Abelsen; Aud Obstfelder (BMC, 2021)
Abstract Background The increased prevalence of chronic diseases and an ageing population challenge healthcare delivery, particularly hospital-based care. To address this issue, health policy aims to decentralize healthcare by transferring responsibility and introducing new services in primary healthcare. In-depth knowledge of associated implementation processes is crucial for health care managers, policymakers, and the health care personnel involved. In this article, we apply an ethnographic approach in a study of nurses' contributions to the implementation of a new inpatient service in an outpatient primary care emergency clinic and explore the competencies involved. The approach allowed us to explore the unexpressed yet significant effort, knowledge and competence of nurses that shaped the new service. Methods The study combines observations (250 h) and several in situ interviews with healthcare personnel and individual in-depth interviews with nurses (n = 8) at the emergency clinic. In our analysis, we draw on a sociological perspective on healthcare work and organization that considers nursing a practice within the boundaries of clinical patient work, organizational structures, and managerial and professional requirements. Results We describe the following three aspects of nurses' contributions to the implementation of the new service: (1) anticipating worst-case scenarios and taking responsibility for preventing them, (2) contributing coherence in patient care by ensuring that new and established procedures are interconnected, and (3) engaging in "invisible work". The nurses draw on their own experiences from their work as emergency nurses and knowledge of the local and regional contexts. They utilize their knowledge, competence, and organizing skills to influence the implementation process and ensure high-quality healthcare delivery in the extended service. Conclusions Our study illustrates that nurses' contributions are vital to coordinating and adjusting extended services. Organizing work, in addition to clinical work, is a crucial aspect of nursing work. It 'glues' the complex and varied components of the individual patient's services into coherent and holistic care trajectories. It is this organizing competence that nurses utilize when coordinating and adjusting extended services. We believe that nurses' organizing work is generally invaluable in implementing new services, although it has not been well emphasized in practice and research.